Embedded observation of science ESP students in South African instructional settings - Ngoepe, Lucia Junia (South African Journal of Higher Education, 2016)
Observation can afford the researcher an opportunity to observe events as they spontaneously occur. It could be used to observe students’ and lecturers’ behaviours in a variety of settings and to collect data on how they use language. This is also a means of assessing what students have or have not learned. Thus, classroom observation is one of the mechanisms for achieving effective teaching and learning. This paper describes real-time observation of 10 English and Study Skills (ESS) English for Specific Purposes (ESP) lectures to under-prepared science students. Embedded observation was one of the mechanisms employed to evaluate the ESS course. The students were taught a science ESP course integrated in a Bachelor of Science Extended Degree Programme (BSc EDP) curriculum at the University of Limpopo (UL), Turfloop Campus. The researcher used an observation scheme to reveal strengths and weaknesses in the lectures, and by extension, the ESS content. Key words: Embedded, observation, ESP, SA, science, students